2022
DOI: 10.1242/dev.200278
|View full text |Cite
|
Sign up to set email alerts
|

A dual involvement of Protocadherin 18a in stromal cell development guides the formation of a functional hematopoietic niche

Abstract: Hematopoietic stem and progenitor cells (HSPCs) emerge from the aorta and migrate to the caudal hematopoietic tissue (CHT) of zebrafish larvae, the hematopoietic equivalent of the mammalian fetal liver, for their proliferation and differentiation. We previously reported that somite-derived stromal cells were a key component of the CHT niche. Here we found that the cell adhesion protein protocadherin-18a (Pcdh18a) is expressed in the stromal cell progenitors (SCPs) emigrating from somites toward the future CHT.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…1E, S4A, S4C). Previous studies have shown that stromal reticular cells arise from the sclerotome and become closely associated with the vasculature in the caudal vein plexus (CVP), where they play a critical role in the hematopoietic stem cell (HSC) development ( 20 , 21 , 30 , 34 ). Consistent with this, we identified a ‘stromal reticular cell’ (SRC) cluster within our dataset, with high-level marker expression ( clec19a , sfrp1a , ccl25b ) in CVP-associated fibroblasts (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1E, S4A, S4C). Previous studies have shown that stromal reticular cells arise from the sclerotome and become closely associated with the vasculature in the caudal vein plexus (CVP), where they play a critical role in the hematopoietic stem cell (HSC) development ( 20 , 21 , 30 , 34 ). Consistent with this, we identified a ‘stromal reticular cell’ (SRC) cluster within our dataset, with high-level marker expression ( clec19a , sfrp1a , ccl25b ) in CVP-associated fibroblasts (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have characterized individual fibroblast populaKons in the trunks of zebrafish embryos. For instance, fibroblasts along the horizontal myosepta 19 and stromal reKcular cells in the caudal venous plexus 20,21 have been shown to regulate lymphangiogenesis and hematopoiesis during zebrafish development, respecKvely. Similarly, tenocytes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4, A and C). Previous studies have shown that SRCs arise from the sclerotome and become closely associated with the vasculature in the caudal vein plexus (CVP), where they play a critical role in the hematopoietic stem cell development ( 20 , 21 , 30 , 34 ). Consistent with this, we identified an SRC cluster within our dataset, with high-level marker expression ( clec19a , sfrp1a , and ccl25b ) in CVP-associated fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have characterized individual fibroblast populations in the trunks of zebrafish embryos. For instance, fibroblasts along the horizontal myosepta (19) and stromal reticular cells (SRCs) in the caudal vein plexus (20,21) have been shown to regulate lymphangiogenesis and hematopoiesis during zebrafish development, respectively. Similarly, tenocytes along the myotendinous junction (MTJ) (22)(23)(24)(25), fin mesenchymal cells in the fin folds (26), and perivascular fibroblasts along intersegmental vessels (ISVs) (27) are known to provide structural support to their respective tissues of residence by depositing ECM.…”
Section: Introductionmentioning
confidence: 99%